Longitudinal relations among exuberance, externalizing behaviors, and attentional bias to reward: the mediating role of effortful control - Morales, Santiago (Dev Sci, 2015)
The present study examined the associations between temperamental exuberance during toddlerhood (20 months), attention bias towards reward at the end of kindergarten (76 months), and externalizing behaviors across the kindergarten year. Moreover, we examined the role of effortful control at 48 months on the relation between early exuberance and attention bias. Attention bias towards reward was positively predicted by exuberance, negatively predicted by effortful control, and positively related to externalizing problems. Finally, the longitudinal path between exuberance and attention bias to reward was mediated by effortful control – such that higher toddler exuberance led to increased attention bias towards reward by way of lower effortful control. These results extend the attention bias and socioemotional functioning literature and have implications for the identification of children at risk for behavioral problems.